Measuring newborn foot length to identify small babies in need of extra care: a cross sectional hospital based study with community follow-up in Tanzania - Penfold Suzanne; Jaribu Jennie; Marchant Tanya; Tanner Marcel; Schellenberg Joanna (BMC, 2010)
Abstract Background Neonatal mortality because of low birth weight or prematurity remains high in many developing country settings. This research aimed to estimate the sensitivity and specificity, and the positive and negative predictive values of newborn foot length to identify babies who are low birth weight or premature and in need of extra care in a rural African setting. Methods A cross-sectional study of newborn babies in hospital, with community follow-up on the fifth day of life, was carried out between 13 July and 16 October 2009 in southern Tanzania. Foot length, birth weight and gestational age were estimated on the first day and foot length remeasured on the fifth day of life. Results In hospital 529 babies were recruited and measured within 24 hours of birth, 183 of whom were also followed-up at home on the fifth day. Day one foot length <7 cm at birth was 75% sensitive (95%CI 36-100) and 99% specific (95%CI 97-99) to identify very small babies (birth weight <1500 grams); foot length <8 cm had sensitivity and specificity of 87% (95%CI 79-94) and 60% (95%CI 55-64) to identify those with low birth weight (<2500 grams), and 93% (95%CI 82-99) and 58% (95%CI 53-62) to identify those born premature (<37 weeks). Mean foot length on the first day was 7.8 cm (standard deviation 0.47); the mean difference between first and fifth day foot lengths was 0.1 cm (standard deviation 0.3): foot length measured on or before the fifth day of life identified more than three-quarters of babies who were born low birth weight. Conclusion Measurement of newborn foot length for home births in resource poor settings has the potential to be used by birth attendants, community volunteers or parents as a screening tool to identify low birth weight or premature newborns in order that they can receive targeted interventions for improved survival